Model Pengukuran Kesehatan Mental pada Mahasiswa di Perguruan Tinggi Islam - Aziz, Rahmat; Mangestuti, Retno; Sholichatun, Yulia; Rahayu, Iin Tri; Purwaningtyas, Endah Kurniawati; Wahyuni, Esa Nur (UIR Press, 2021)
The view that mental health can only be understood with a single approach can explain the existing phenomena. This paper aims to provide an alternative measurement model in conducting studies on student mental health. Data were obtained from 840 students at four state Islamic universities in East Java. Data was collected through the mental health scale. The percentage technique was used to examine the level and profile of mental health, while the variance analysis technique was used to investigate the differences between men and women. The analysis results show that the subjects have a high level of mental health and have a minimum mental illness profile. There was no evidence of a difference between men and women in terms of mental health. The results of this study have implications for the use of mental health measuring tools to be used as an alternative in measuring mental health.